Analisis Implementasi Manajemen Pendidikan dalam Meningkatkan Mutu Pendidikan Ponpes Modern Alkautsar Askandariyah Srono Banyuwangi: Analysis of the Implementation of Educational Management in Improving the Quality of Education at the Modern Islamic Boarding School of Alkautsar Askandariyah Srono Banyuwangi - Yani Eka Putri; Untung Lasiyono; Taudlikhul Afkar (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Alkautsar Askandariyah Modern Islamic Boarding School, Banyuwangi, has unique characteristics by combining the study of classical texts (yellow books) with general knowledge, while also equipping students with Arabic and English language skills. Efforts to improve the quality of education at this Islamic boarding school require structured management oriented toward both academic development and character building. This study employs a descriptive qualitative method with data collection techniques that include observation, in-depth interviews, and documentation. Informants were selected purposively, consisting of caretakers, leaders, teachers, and students. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. Educational management at this Islamic boarding school is carried out through four main stages: planning, organizing, implementing, and monitoring. Planning is guided by the "Pancajiwa" vision and mission and supported by an integrated curriculum. Organization is established through a hierarchical structure with a clear division of tasks. Program implementation includes the sorogan method, bandungan method, bilingual programs, and international classes. Supervision is conducted through periodic evaluations, academic competitions, and psychological assistance. The improvement of educational quality at Alkautsar Askandariyah Modern Islamic Boarding School is supported by strong, adaptive, and holistic management. This success requires attention not only to academic achievement but also to character development and the emotional well-being of students, despite challenges such as student adaptation and restrictions on device use. The implementation of the sorogan method, bandungan method, bilingual program, and international class has been proven to improve students’ academic and language competencies.